From the general to the situated: three decades of metacognition - Georghiades, Petros (International journal of science education, 2004)
This paper discusses the notion of metacognition, which is usually defined as 'cognitions about cognitions', or 'thinking about one's own thinking'. In so doing, it reviews the literature on metacognition over the past three decades, listing different definitions of the term and identifying diverse origins of processes metacognitive. Aspects of the nature of metacognition are discussed, highlighting some of its important yet problematic dimensions, and the potentially positive impact metacognition can have on the learning process is addressed. The paper also relates metacognition to the broader area of general thinking skills and discusses the appropriateness of practising metacognition with primary school children. The paper concludes with a synopsis of research in the outcomes of metacognition, in general, and in science education, in particular, highlighting recent interest in blending metacognitive thinking with science subject matter. Directions for research in science education with an interest in metacognition are also proposed.